Investigating the Youth Sports Development Pathway Within a South African Context - van den Berg, Liandi; Jonck, Petronella; Surujlal, Jhalukpreya (Frontiers in Psychology, 2021)
The past two decades witnessed increased participation in professional as well as amateur sport, giving impetus to concomitant amplified interest in long-term athlete development (LTAD). LTAD has been described as the structured and progressive growth of an athlete through different stages of development resulting in some athletes achieving elite sport status. Furthermore, the interest in athletic career development from a holistic perspective has contributed to management approaches underscoring sustainable talent development and participation in sport. The current study investigated youth sports development pathways through both models of development within a South African context. A descriptive quantitative cross-sectional design was used to generate a convenient sample of athletes (N = 267). The Talent Development Environment Questionnaire (TDEQ) was administered, which in previous studies produced acceptable psychometric properties. Principal factor analysis, confirmatory factor analysis, Monte Carlo parallel simulation, MANOVA and hierarchical regression were performed to analyse the data. The TDEQ was validated for the South African context and was found to measure four components, namely supportive and challenging environment, development fundamentals, support networks, and long-term development. Respondents in the various developmental categories of novice, advanced and elite student-athletes were not statistically significantly influenced by any of the four factors. Controlling for the talent developmental phase, the model proposed did not statistically significantly predict the development pathway of youth athletes. The results provide evidence with some practical significance as supportive and challenging environment and long-term development focus reported a small effect. Further research is warranted to develop a more suitable measuring instrument to measure the talent development pathway within the investigated athlete environment.